KaiC family ATPases in the nonheterocystous nitrogen-fixing cyanobacterium Leptolyngbya boryana - Yusuke Matsukami; Katsuaki Oyama; Chihiro Azai; Yasuhiro Onoue; Yuichi Fujita; Kazuki Terauchi (Scientific Reports)
Abstract A circadian clock is reconstituted in vitro by incubating three proteins, KaiA, KaiB, and KaiC from the non-nitrogen-fixing cyanobacterium Synechococcus elongatus PCC 7942 in the presence of ATP. Leptolyngbya boryana is a filamentous cyanobacterium that grows diazotrophically under microoxic conditions. Among the aforementioned proteins, KaiC is the main clock oscillator belonging to the RecA ATPase superfamily. Genomic studies have revealed the presence of many genes encoding KaiC family ATPases in archaea and bacteria; however, very few have been analyzed in detail. For example, the L. boryana genome encodes two kaiC homologs designated as LbkaiC1 (LBWT_14830) and LbkaiC2 (LBWT_17950). LbKaiC1 is highly similar to KaiC from S. elongatus PCC 7942 compared with LbKaiC2. LbKaiC1 and LbKaiC2 were purified as Strep-tag fusion proteins. LbKaiC1 formed a hexamer and exhibited autophosphorylation, autodephosphorylation, and ATPase activities. Furthermore, it exhibited circadian phosphorylation rhythm in the presence of KaiA and KaiB from S. elongatus PCC 7942, indicating that LbKaiC1 is the central oscillator of the circadian clock in L. boryana. The temporal separation of nitrogen fixation from photosynthesis may be supported by the circadian rhythm generated by LbKaiC1 in L. boryana. LbKaiC2 had low ATPase activity, which depended on temperature, and its autophosphorylation activity was not detected like a circadian oscillator KaiC. Although the function of LbKaiC2 remains unknown, this work will provide comprehensive understanding of KaiC family ATPases.